1987
DOI: 10.1159/000457747
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Neonatal Effects of the Beta-Adrenoceptor Blocking Agents

Abstract: The placental transfer of beta-adrenoceptor blocking agents has been well established in the last years. Randomized and/or controlled studies have given a less pessimistic view of the consequences of these drugs on the fetal and neonatal adaptation. In fact, the beta-blockers are able to produce hypotension, bradycardia, respiratory troubles in the newborn infant, troubles which are generally slight when the neonates are full-term. However, even if in good clinical conditions, this kind of neonate should be ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 11 publications
0
13
2
1
Order By: Relevance
“…However, adverse effects of 0-receptor blocking drugs in the human infant have also been a source of concern (29,30), so our results suggest that caution should be exercised in the passive administration of Padrenergic drugs such as ritodrine to the fetus over prolonged periods of time. Such infants should clearly be provided with the same level of care as that recommended for infants from Pblocked pregnancies (30).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, adverse effects of 0-receptor blocking drugs in the human infant have also been a source of concern (29,30), so our results suggest that caution should be exercised in the passive administration of Padrenergic drugs such as ritodrine to the fetus over prolonged periods of time. Such infants should clearly be provided with the same level of care as that recommended for infants from Pblocked pregnancies (30).…”
Section: Discussionmentioning
confidence: 93%
“…Although there has been concern about possible cardiovascular complications in the fetus from P-sympathomimetic therapy for tocolysis (23) and effects of p-agonists on the incidence or respiratory distress and perinatal hypoglycemia (l,28) have been reported, the incidence of long-term complications appears low (28). However, adverse effects of 0-receptor blocking drugs in the human infant have also been a source of concern (29,30), so our results suggest that caution should be exercised in the passive administration of Padrenergic drugs such as ritodrine to the fetus over prolonged periods of time. Such infants should clearly be provided with the same level of care as that recommended for infants from Pblocked pregnancies (30).…”
Section: Discussionmentioning
confidence: 99%
“…␤ -Blockers cross the placenta and reach the fetus at concentrations very close to those present in the pregnant mother [70] . Our study provides evidence that ␤ AR blockers, particularly ␤ 1 AR antagonists, exacerbate hypoxia-induced bradycardia in the early fetus.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Several controlled studies have shown their efficacy and safety in pregnant women, without any specific risk for the fetus (Dubois et al 1983;Fidler et al 1983;Livingstone et al 1983;Olofsson et al 1986;Plouin et al 1988). However, very little information is available (for review: see Morselli et al 1989) on the pahrmacokinetics of these agents in the neonate, or on the possible relationship between neonatal drug concentrations and the cardiovascular effects observed in a limited number of cases 48-72 h after birth (Boutroy et al 1987).…”
Section: Discussionmentioning
confidence: 99%